Любимые сказки народов Урала и Поволжья - Гарипов Менсадык Гарипович (Удмуртия, 2022)
Экземпляры: ЦБ; 16; 22; 8; 31; (20230619) / Инвентарный номер: 98680 / Цена: / Сис.шифр: 82.3(235)-6 / Авт.знак: Л 93 / ГРНТИ: 17.71.91 / ББК: 82.3(235)-6